Recognizing the Common Origins of Dystonia and the Development of Human Movement: A Manifesto of Unmet Needs in Isolated Childhood Dystonias - Lin, Jean-Pierre; Nardocci, Nardo (Frontiers in Neurology, 2016)
Dystonia in childhood may be severely disabling and often un-remitting and un-recognised. Considered a rare disorder, dystonic symptoms in childhood are pervasive in many conditions including disorders of developmental delay, cerebral palsy, autism, neurometabolic, neuroinflammatory and neurogenetic disorders. Collectively, there is a need to recognise the role of early postures and movements which characterise phases of normal fetal, infant and child development as a backdrop to the many facets of dystonia in early childhood neurological disorders and to be aware of the developmental context of dystonic symptoms. The role of co-contraction is explored throughout infancy, childhood, young adulthood and in the elderly. Under-recognition of pervasive dystonic disorders of childhood, including within cerebral palsy is reviewed. Original descriptions of cerebral palsy by William Gowers are reviewed and contemporary physiological demonstrations are used to illustrate support for an interpretation of the tonic labyrinthine response as a manifestation of dystonia. Early recognition and molecular diagnosis of childhood dystonia where possible is desirable for appropriate clinical stratification and future precision medicine and functional neurosurgery where appropriate.